miRNA networks regulating gene expression in response to tension or compression forces in the cells of the periodontal ligament - Bonilla Valverde, Mariana (2023)
In response to force application, biological reactions occur in the periodontal ligament that causes the orthodontic tooth movement. Differential expression of genes such as ALPL, FGF7, PDRM1, and NR4A2 are involved in the exposure to tension or compression forces by contributing to bone remodeling. In this study, a systems biology approach is used in order to identify a modulator of gene expression when mechanical loadings are applied in periodontal ligament cells. We developed a mathematical model of the interaction network of ALPL and FGF7 with several miRNAs and the transcription factor modulators in BioNetUCR, Cytoscape and COPASI software. We found that miR129-2 has a negative control in ALPL, FGF7, NR4A2 and PRDM1 genes, while miRNA192 has a negative control in ALPL and FGF7 genes in compression and tension side. Both miRNAs are proposed for future experimental validation.